A benzo[a]phenazine-based redox species with highly reversible two-electron reaction for aqueous organic redox flow batteries. (20th January 2023) - Park, Junyoung; Lee, Youngho; Yun, Deokhee; Kim, Doeun; Hwang, Gyungmin; Han, Byeongjik; Kim, Yongbeom; Jung, Jaehyun; Jeon, Joonhyeon
Highlight: A novel organic redox species (BHPS, C16 H10 N2 O4 S) is created for aqueous RFBs Targeted attachment of -SO3 H and –OH induces high chemical stability and reversibility. Introducing -SO3 H and –OH allows fast redox kinetics and high diffusion coefficients BHPS dipole moment/kinetics/solubility is 9.8/1.8/98.1 times higher than with only –OH. High discharge capacity retention of 99.3% yields current efficiency of 99.5%. Abstract: In aqueous organic redox flow batteries (AORFBs), the inherent problems, such as low energy and poor chemical stability, remain obstacles to the growth of AORFBs for the large-scale energy storage system (ESS). To address these challenges, this paper describes a novel benzo[a]phenazin-5-ol methanesulfonate (BHPS, C16 H10 N2 O4 S) containing sulfonic acid and hydroxyl functional groups, which undergoes a highly stable and reversible two-electron redox reaction in aqueous media, and allows high chemical stability, superb conductivity, high redox potential (−0.943 V) and excellent solubility. The superior chemical and electrochemical properties of the proposed BHPS are demonstrated through various experiments, including full cell-cycling tests, along with theoretical molecular analysis. Experimental results show that the BHPS with highly conductive sulfonic acid group (along with hydroxyl group) leads to 1.83 times higher kinetic constant (1.32 × 10 −3 cm s − 1 ) and 98.07 times higher solubility (1.47 M) than the benzo[ a ]phenazine-5-ol (HBP, C16 H10 N2 O). Further, the BHPS/Fe(CN)6 flow-cell cycling for 100 cycles at 60 mA cm −2 results in great coulombic and energy efficiencies of average 99.5 and 81.9%, along with dramatic charge-and-discharge capacity retention ratios of average 99.79 and 99.25% with initial charge and discharge capacities of 49.11 and 48.76 mAh, respectively. The BHPS successfully synthesized by the attachment of the sulfonic acid and hydroxyl groups to benzo[ a ]phenazine provides a promising anodic organic species for highly efficient AORFBs, and its performance can be further optimized by molecular engineering. Graphical abstract: Image, graphical abstract